A prática constante-aleatória: efeitos da manipulação do aspecto da habilidade e o tipo de perturbação no processo adaptativo em aprendizagem motora - Joao Vitor Alves Pereira Fialho (2007)
The aim of this study was to investigate the effect of constant-random practice, with manipulation of different skill aspects, on adaptation of different types of perturbation in adaptive process of motor learning. Three experiments, composed by two phases (stabilization and adaptation), were conducted. The stabilization phase was divided in two stages: one with constante practice and another with random practice, which guided the three formed groups with perceptive, motor and perceptive-motor skill aspect variation, respectively. After that, the adaptation phase started with one type of perturbation in each experiment. In the first experiment was inserted a perceptive perturbation, in the second a motor perturbation and in the third a perceptive-motorperturbation. Undergraduate students participated in this study and performed a task that consisted of touch sensors in a pre-determinate sequence in integration with a visual stimulus. The measures used in this study were divided in performance measures (absolute error, variable error, constant error and reaction time magnitude and variability), skill microstructure measures (overall movement time magnitude andvariability), skill macrostructure measures (five components relative time magnitude and variability) and complementary measures (trials to achieve the performance criterion and eliminated subjects). Altogether, the results of the three experiments allowed conclude that: a) there is a hierarchi of difficulty in relation to the skill aspect manipulated in random practice, with the practice varying the perceptive-motor aspect being more difficult than the practice varying the motor aspect, and with the practice varying the motor aspect being more difficult than the practice varying theperceptive aspect; b) there is a hierarchi in relation to the type of perturbation, with the perceptive perturbation being more easy than the motor and perceptive-motor perturbation, and the motor perturbation being more easy than the perceptive-motor perturbation; c) it seems to have one relation of specificity between the perturbation ability adapt and the skill aspect manipulated in random practice.